2013
DOI: 10.1128/jcm.03105-12
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Identification of Clinical Yeast Isolates by Use of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: Matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS)-based identification is being adopted by clinical laboratories for routine identification of microorganisms. To date, the majority of studies have focused on the performance and optimization of MALDI-TOF MS for the identification of bacterial isolates. We review recent literature describing the use of MALDI-TOF MS for the routine identification of a variety of yeasts and yeast-like isolates. Specific topics include the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 49 publications
(90 reference statements)
1
40
0
3
Order By: Relevance
“…MALDI-TOF MS has been applied successfully to identify Cryptococcus species, including varieties and hybrids, Candida albicans and non-albicans Candida species, and rare pathogenic yeasts (29,30,(38)(39)(40)(41)(42)(43)(44). Non-Candida species isolates, such as Geotrichum, Galactomyces, Saprochaete, Magnusiomyces, and Trichosporon spp., are underrepresented in the reference library and thus MALDI-TOF MS identification runs were less successful, resulting in low identification rates or failure of reliable analysis (36,45). Our data showed a high level of discriminatory power for MALDI-TOF MS, providing reliable identification of both ascomycetous and basidiomycetous arthroconidial yeasts.…”
Section: Discussionmentioning
confidence: 80%
“…MALDI-TOF MS has been applied successfully to identify Cryptococcus species, including varieties and hybrids, Candida albicans and non-albicans Candida species, and rare pathogenic yeasts (29,30,(38)(39)(40)(41)(42)(43)(44). Non-Candida species isolates, such as Geotrichum, Galactomyces, Saprochaete, Magnusiomyces, and Trichosporon spp., are underrepresented in the reference library and thus MALDI-TOF MS identification runs were less successful, resulting in low identification rates or failure of reliable analysis (36,45). Our data showed a high level of discriminatory power for MALDI-TOF MS, providing reliable identification of both ascomycetous and basidiomycetous arthroconidial yeasts.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have reported that matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) is an accurate, rapid, and inexpensive method for identification of clinically relevant yeasts (10,11). In our previous study, we evaluated the performance of the Vitek MS system (bioMérieux, France) for identifying yeast isolates collected as part of the CHIF-NET program in 2011 (12).…”
mentioning
confidence: 99%
“…Mayaların MALDI-TOF MS ile identifikasyonu öncesinde yaklaşık 25 dakika süren bir ekstraksiyon aşaması gerçekleştirilmesi gerekli olmakla birlikte, bazı araştırmacılar buna alternatif olan ve daha kısa süren yöntemler geliştirdiklerini bildirmişlerdir (13)(14)(15)(16)(17)(18)(19) .…”
Section: Discussionunclassified